Utjecaj Zakona o finansijskoj konsolidaciji privrednih društava na održivost poslovanja kompanija u Federaciji BiH – TK / Influence of the Law of Financial Consolidation Business Subject to Established Secure Business of Company in the Federation Bosnia and Herzegovina - TK - Čokić-Džinić, Mirela (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
The process of financial consolidation in any way can be one of the painstaking processes to potential or existing crisis in the market, which is usually according with insolvency. Namely, on the one hand, it is a financial consolidation of companies at the entity level that inevitably reflected to the country, while on the other hand, this process had to appear as a necessary consequence of all previous financial consolidation at the global level. Thus, guided by the experience of the current economy and the impact of the process of fiscal consolidation in some countries we will detail and analytical show grounds for his part "positive" application in one of the entities FBiH, more precisely in the area of Tuzla Canton (TK). The author of this work is of the opinion that all financial consolidation processes in general, and at the state level but also successively contribute, if anything, the fusion of the financial statements and the improvement of financial conditions that ultimately result in particular successfully implemented procedures, which step by step in a certain percentage part, can contribute to development.